Transcriptome characterization and profiling related to detoxification enzyme genes in Chilo sacchariphagus (Lepidoptera Crambidae). Issue 9 (7th September 2022) - Liu, Jianbai; Yi, Jiequn; Wu, Han; Lu, Yinglin; Mao, Yongkai; Lin, Mingjiang; Li, Jihu; An, Yuxing
Abstract: Chilo sacchariphagus Bojeris is one of the most dangerous pests of sugarcane. The larvae damage the seedlings and stems of sugarcane and also harm sorghum, corn and other crops, which causes great economic losses to the sugar industry every year. Transcriptome sequencing and expression profile analysis of cytochrome P450 monooxygenase (CYP), carboxylesterase and glutathione S‐transferase (GST) were carried out, which could provide a basis for drug resistance monitoring and drug resistance management of the pest. Unigenes of C. sacchariphagus were obtained by using the Illumina HiSeqTM 4, 000 platform as 150 bp paired‐end reads. A total of 173, 013 unigenes were obtained after data assembly and redundancy removal. 28, 330 unigenes were annotated based on multiple public databases, and the number of unigenes annotated by NR database was the largest. According to the transcriptome analysis, 214 candidate detoxification enzyme genes were identified, including 44 GSTs, 138 CYPs, and 32 CarEs . Phylogenetic analysis showed that the CYPs were mainly clustered in CYP4, CYP6, CYP9 and CYP12 subfamilies; CarEs mainly include antennal CarEs, venom CarEs and CarEs NOTUM; while the GSTs cluster mainly contains subfamilies such as delta, omega, epsilon, theta, zeta and sigma. In this study, transcriptome information of C. sacchariphagus was obtained, and genes related to detoxification were identified, which could provide data and a basis for the further study of detoxification and host plant adaptation mechanism of C. sacchariphagus .